INFOGRAPHIC FOR PREGNANT WOMEN AND CAREGIVERS: EDUCATIONAL TECHNOLOGY IN THE CONTEXT OF OBSTETRIC CARE - Oliveira, Yany Suellen Pereira Cruz; Costa, Roberta; Lima, Margarete Maria de; Velho, Manuela Beatriz; Gomes, Iris Elizabete Messa; Wilhelm, Laís Antunes; Coelho, Luana Pereira Ibiapina (Cogitare Enfermagem, 2023)
Objective: to describe the process of construction and validation of an educational infographic with guidelines for pregnant women and companions in obstetric care in the context of Covid-19. Method: methodological research based on Instructional System Design guidelines and conducted from January 2021 to March 2022, in the State of Santa Catarina - Brazil, in three moments: scoping review, interviews with nurses from an Obstetric Emergency, and elaboration of educational technology and validation with experts. The analysis was anchored in content analysis with Content Validity Index. Results: the infographic addresses care for the prevention of Covid-19 infection, guidance on the onset of labor, when to seek maternity care, and care during hospitalization of pregnant women. The infographic obtained a Content Validity Index of 83.3%. Conclusion: educational technology was considered adequate for disseminating information and assisting professionals in promoting health and preventing injuries to the obstetric population.